More than a feeling: Tactile exploration informs relative size perception. (September 2022) - Stevens, Jennifer
Esref Armagan is a blind painter. Cognitive and neural scientists have described his use of line structure when drawing and his visual cortex activation during tactile exploration. But what remains unknown is how Esref, without ever having sight, may be able to understand the use of depth cues such as relative size in a picture. To examine whether tactile experience provides information about relative size, we blindfolded sighted individuals and asked them to haptically explore a set of objects in either near or far locations before drawing the objects on paper. Objects explored with an arms extended position were drawn significantly smaller than those explored just in front of the face. Our results provide the first evidence that haptic object interaction can provide information about relative size, akin to that garnered visually. It can be used to inform spatial layout or, in Esref's case, to artistically render objects in three dimensions.